Neuregulin-1β, Biomarkers of Inflammation and Myocardial Fibrosis in Heart Failure Patients - K. A. Zhbanov; E. Yu. Salakheeva; I. Ya. Sokolova; E. A. Zheleznykh; V. Yu. Zektser; E. V. Privalova; Yu. N. Belenkov; A. A. Shchendrygina (Рациональная фармакотерапия в кардиологии)
Neuregulin-1β (NRG-1) is an emerging biomarker of heart failure (HF). The mechanisms of its action in HF patients are yet  to be investigated. Cardioprotective and anti-inflammatory  effects of NRG-1 have been reported.Aim. To assess NRG-1 levels in HF patients and investigate the association between NRG-1 and biomarkers of inflammation and myocardial fibrosis.Material and Methods. NRG-1, biomarkers of inflammation and fibrosis (hsCRP, IL-6, sVCAM-1, MMP-9, Galectin-3, ST2, TGF-β) were assessed in 47 patients with HF and preserved ejection fraction (HFpEF); 39 patients with HF and reduced ejection  (HFrEF) and 40 healthy participants. The associations between  NRG-1 and biomarkers of inflammation and fibrosis, as well as  the composite outcomes of cardiovascular death and HF  hospitalisations were assessed.Results. Median NRG-1 levels in HFpEF were 0.969 (0.348; 1.932) ng/ml, in HFrEF – 0.63 (0.348; 1.932), in healthy participants 0.379 (0.195; 0.861) ng/ml, and was significantly higher in HFpEF compared to healthy volunteers (р=0.004). There was no  difference in NRG-1 concentration between HFpEF and HFrEF. In  HF patients, all biomarkers of inflammation and fibrosis were  higher than in controls. ST2, IL-6 and TGF-β were significantly higher in HFrEF compared to HFpEF patients, while hsCRP,  sVCAM-1, MMP-9, and Galectin-3 levels were comparable. In  HFpEF, NRG-1 was associated with hsCRP (rs=0.378, p=0.023) and IL-6 (rs=0.378, p=0.014). Median follow-up time in patients with HFpEF and in patients was 312 (236; 388) days, in HFrEF – 147 (98; 237) days. In HFpEF, 2 patients died and 19 were  hospitalized due to HF. In HFrEF, 10 deaths and 19  hospitalizations were registered. Kaplan-Mayer analysis showed that HFpEF patients with increased NRG-1 and IL-6 had higher  levels of HF hospitalisation (log rank test, р=0.046 and р=0.012, respectively). In a multivariable cox proportional hazard model,  the association between the NRG-1 and outcomes remained significant after adjustment for age, gender and NTproBNP but diminished when hsCRP and IL-6 were included in the model.Conclusion. NGR-1 level significantly higher in HFpEF compared to healthy participants, and comparable with NRG-1 concentrations in HFrEF. In HFpEF, NRG-1 was associated with biomarkers of inflammation and fibrosis. The prognostic value of NRG-1 in HF requires further investigations.